The practices of Enterprise Risk Management (ERM) in Small and Medium Enterprises (SMES) – A literature review / Nadhrah Manas, Norhayati Mohmad Zakwan @ Zakuan and Mariam Setapa - Manas, Nadhrah; Mohmad Zakwan @ Zakuan, Norhayati; Setapa, Mariam (2021)
Small and Medium Enterprises (SMEs) have been the backbone of economic growth in most countries, particularly in emerging countries, and they continue to play a vital role. When compared to large corporations, SMEs had the highest proportion of job creation, highest revenue growth, and highest employment growth, according to the research of 49,370 businesses in 104 countries based on the World Bank Enterprise Surveys (ES) database (Ayyagari et al., 2011). In Malaysia, there is a wide range of SME industries that contribute to the country's GDP by representing the total number of businesses in various sectors. As a result, these industries had a considerable impact on the country's economic growth. These industries have become the most important to the country's economy because of prior contributions to SMEs; the government has taken initiatives to encourage these industries in terms of SMEs development (Stern and Loeprick, 2007). Thus, SMEs are one of the largest industries, encompassing a wide range of businesses such as trading, services, manufacturing, and agriculture. Hence, in many nations, SMEs account for 90 percent of all business establishments. Similarly, according to the Department of Statistics Malaysia (DOSM) (2020), Malaysian SMEs account for around 97.2 percent of the country's total establishments.